Tihei mauri ora – contact, culture, and context. (3rd April 2022) - Tudor, Keith; Rodgers, Brian; Smith, Valance
ABSTRACT: This article introduces and elaborates on the themes of PCE2021: 'Tihei mauri ora – Contact, culture, and context'. It provides the background to the organizers' thinking about these themes, and especially their focus on bicultural engagement in the context of life and therapeutic practice in Aotearoa New Zealand and, as such, offers an introduction to this special issue of papers from that conference.